Awareness, Willingness, and Concerns Regarding the HPV Vaccine in Rawalpindi District and Islamabad Capital Territory - Hafeez, Yumna; Hafeez, Ilsa; Zeb, Shazia; Sattar, Raana; Rubab, Sadia; Fatima, Farzana (Journal of Rawalpindi Medical College, 2025)
Objective: To evaluate awareness, willingness, and concerns regarding the HPV vaccine among parents and guardians in Rawalpindi and Islamabad. Methods: A cross-sectional survey was conducted among 1,007 respondents. Data on demographics, HPV awareness, willingness to vaccinate daughters, and concerns were analyzed using descriptive statistics. Comparative analysis was performed by stratifying responses based on education level and HCW status. Results: Awareness of the HPV vaccine was reported by 66.2% of respondents, while 42.3% were willing to vaccinate their daughters. Safety perceptions were mixed: 40.6% considered the vaccine safe, 37.2% were unsure, and 22.1% believed it was unsafe. The most common concerns were side effects (43.1%), infertility (28.8%), vaccine effectiveness (21.5%), and quality (21.4%). HCWs demonstrated significantly higher awareness (88.3% vs. 48.3% for Non-HCWs) and willingness (63.9% vs. 24.7%). A direct, positive correlation was observed between higher education and both awareness (from 38.1% in the Low education group to 89.2% in the Postgraduate group) and willingness (from 20.5% to 59.7%). Despite these concerns, 42.1% supported inclusion of the HPV vaccine in Pakistan’s Expanded Programme on Immunization (EPI). Conclusion: A substantial gap exists between HPV vaccine awareness and definitive acceptance in the twin cities of Rawalpindi and Islamabad. Misconceptions regarding side effects and infertility represent significant barriers. While HCW status and higher education strongly predict acceptance, targeted public health campaigns are urgently needed to dispel misinformation, specifically addressing the safety and effectiveness of the vaccine, to ensure the success of the newly launched national HPV immunization program. Keywords: Cervical cancer, HPV, health concern, Immunization, Public Awareness